Odpowiedzi

2009-12-15T21:03:15+01:00
A = 5cm, b = 6cm, c = 7 cm
korzystamy z wzoru Herona
p =(a+b+c)/2 =(5+6+7)cm :2 = 18cm :2 = 9 cm
p-a = 9cm - 5cm = 4cm
p-b = 9cm -6cm = 3 cm
p-c = 9cm - 7 cm = 2cm
A =p(p-a)(p-b)(p-c) = (9*4*3*2) cm^4 = 216 cm^4
P = √A = √(216 cm^4) ≈ 14,7 cm²
Odp. P ≈ 14,7 cm²
P =[a*h1]/2
2P = a*h1 ---> h1 = [2P]/a
h1 = [2*14,7 cm²]/5cm = 29,4 cm²/5cm = 5,88 cm ≈ 5,9 cm

Odp. h1 ≈ 5,9 cm
Dokładnie:
P = √216 cm² = √(36*6) cm² = 6√6 cm²
h1 = 2P/a = 12√6/5 cm
h2 = 2P/6 = 12√6/6 cm = 2√6 cm
h3 = 2P/7 = 12√6/7 cm
1 4 1